Host And Temperature Preferensce, Male Occurrence And Morfomentrics Offungivorous Nematode, Aphelenchus Avenae Isolates From Japan - Buni Amin (Agricultural Faculty, 2007)
ABSTRACT.Host and temperature preference, male accurrence, and morfomentrics of 39 isolates of Apehelenchus avenae were investigated. Of the 39 isolates, 33 were from 7 sistrict of Kyushu, 3 preference were investigated on 4 species of fungi; Botrytis cinerea, Rhizoctonia solani AG-4, Fusarium oxysporum f. sp. Melonis, and Pyitum aphanidermatum growing on 1/5 strength PDA medium. The nematodes were incubated on respective fungus mat for 30 days at 25 and 30 OC host fungi and temperatures gave rise to various levels of reproduction and male accurance. The isolates were divided into 5 groups based on their reproductivity on their host fungi at the 2 temperature regimes. Most of the isolates of A. avenae progated themselves at 25 0C on B. cinera and R. solani AG-4, was 60.850 given by Nagasaki isolates (NA3). The maximum multiplication 48.420 at 0C accured on R. solani byu Kagoshima isiolate (KA3). The occurrence of males was very low in all isolates and it occurred only at 30 0C. De Mans value of body dimension were measured and showed no significant variation among the isolates. Besides, There were no realtions between groupings by host preference and by body dimension.